REALITAS KEHIDUPAN KAKURE KIRISHITAN PADA ZAMAN EDO DI JEPANG - Rahmini susanti parapat (Jurnal Pustaka Nusantara dan Budaya, 2013)
Culture is the result of human cultivation manifested in behavior use the library research. A part of culture is about religion. In this paper, the author analyzes using using history theory , and also qualitative method. In this paper, specifically discusses about reality of Kakure Kirishitan’s life that took place in the reign of Tokugawa. Christianity is a religion whose the existence is forbidden and strongly opposed by Tokugawa government. Beliefs held by Kakure Kirishitan is syncretic nature of trust, which forms a complex mixture between Christianity, Buddhism, Shinto, and folk beliefs or objects, language, symbols, etc, which surround humans that affect the behavior and human action. Search the data in this paper. Based on this history theory, the results of this study is strengthen the theory, that the history theory is the attemp to trace the origin and growth of religious ideas and institutions trough definite periods of historical development and to asses the role of forces with religion contended during these periods.